Epigenetic manipulation to improve mouse SCNT embryonic development - Li, Yamei; Sun, Qiang (Frontiers in Genetics, 2022)
Cloned mammals can be achieved through somatic cell nuclear transfer (SCNT) which involves the reprogramming of differentiated somatic cells into a totipotent state. However, low cloning efficiency hampers its application severely. Cloned embryos have the same DNA as donor somatic cells. Therefore, incomplete epigenetic reprogramming accounts for the low development of cloned embryos. In this review, we describe recent epigenetic barriers in SCNT embryos and strategies to correct these epigenetic defects and avoid the occurrence of abnormalities in cloned animals.